Analysis of The Effect of The Administration of Communications Towers in The Selling Prices of Residential Real estate )New University Village Model( - حمد ايوب انور (Journal of Economics and Administrative Sciences, 2016)
Abstract Should be the goal of Government controls, including environmental controls and safety laws to protect citizens from the harmful effects of negative secreted by human’s additions and changes in the environment. and perhaps the protection aspects of the protection of citizens from the adverse effects of communications towers, including those produced by towers of health effects. The people the right to choose the nature of the physical environment, which should not be imposed on them by others. Communications towers are one of the main problems that have been imposed on the people in the village new University in the city of Erbil, which started to take serious economic and social dimensions, and influence the decision-making process in the real estate market in the study area. In light of this research analyzes the impact of establishment of communications towers in the selling prices of residential properties in the village new University in the city of Erbil ,Search targeted analysis and describe the impact of the establishment of communications towers in the selling prices of residential properties in the village new University in the city of Irbil. Through the search results show a clear, negative impact to establish communications towers in the prices of residential properties in the study area, and finally finished searching a set of important recommendations, including the need to control the communications towers at the micro-level and macro-level, at the micro level by choosing the towers less influential environmental effects. And at the macro level by selecting the location and conditions of the administration of communications towers in all the cities, through legislation and environmental protection laws and taxation and environmental awareness